Inflation and monetary regimes - Gerald P. Dwyer; Mark Fisher (Federal Reserve Bank of Atlanta, 2009)
Correlations of inflation with the growth rate of money increase when data are averaged over longer time periods. Correlations of inflation with the growth of money also are higher when high-inflation as well as low-inflation countries are included in the analysis. We show that serial correlation in the underlying inflation rate ties these two observations together and explains them. We present evidence that averaging increases the correlation of inflation and money growth more when the underlying inflation rate has higher serial correlation.
Keywords: E31; E5; 330; money and inflation; inflation; quantity theory; Inflation; Geldmengensteuerung; Quantitätstheorie; Theorie; Schätzung; Welt